59Co Internal field NMR analysis of Co35Fe35Ni30 alloy synthesized via novel low cost chemical reduction technique. (January 2021) - Reddy, G. Srinivasa; Manjunatha, M.; Ramesh, K.P.
Abstract: We have synthesized ternary cobalt alloy using a chemical reduction process using hydrazine as a reducing agent . X-Ray Diffraction (XRD) measurements shows that the synthesized cobalt ternary alloy exists in the pure face centred cubic ( fcc ) phase with lattice parameter of 3.5562 ± 5 Å. The SEM micrograph shows that the particles exist in the spherical shape which suggests that the particles are crystallized in fcc phase. The magnetic properties are determined using Vibrating Sample Magnetometry (VSM) and 59 Co IFNMR technique. The saturation magnetization ( M S ) of the synthesized sample is 80 emu/g, a slightly lower value compared to the pure cobalt metal. 59 Co IFNMR technique shows that there is a broad distribution of hyperfine field ( 6 T) compared to the pure fcc cobalt metal. Further, from the deconvoluted NMR peaks suggests that the variation in the nearest neighbours to the central cobalt atom leads to the different hyperfine field. Highlights: Phase pure ternary alloy (Co35 Fe35 Ni30 ) is synthesized via novel low cost chemical reduction technique. The synthesized material exhibits fcc structure with lattice constant of 3.5562 ± 5 Å. VSM studies confirm the decrease in the saturation magnetization (MS ) compared to pure metallic cobalt. 59 Co NMR studies demonstrates the broad distribution of hyperfine field compared to pure fcc metallic cobalt. The Co–Ni interaction leads to decrease in the hyperfine field and Co–Fe interaction increases the hyperfine field.